Combining Tense and Temporal Extension: The Potential of Bergson’s ‘Qualitative Multiplicity’ for Conquering Problems of (Analytic) Time Metaphysics. - Deppe, Sonja (bergsoniana, 2021)
The article confronts Bergson’s Time and Free Will with ontological models of temporal reality from analytic time metaphysics, such as presentism, eternalism etc. I maintain that tense (and hence a changing “now”) and temporal extension are crucial features for understanding successive structure within our temporal experience. In the context of analytic metaphysics following McTaggart, however, tense and extension fall under the suspicion that they are not consistent with each other. I show Bergson’s concept of “Qualitative Multiplicity” to open a new perspective on the issue: being introduced as a qualitative and hence not countable or measurable feature, it enables an understanding of temporal extension that differs radically from spatial extension. Following this, we can understand Bergson’s durational realm of the conscious I as temporally extended in qualitative but not numerical respect — which, in turn, is unproblematically consistent with tense. A second issue of the article is a critical reflection on the conception of the external world established in Time and Free Will: I maintain that it is not problem-free to conceive any part of reality as merely tensed and not at all temporally extended. I conclude this to be a strong motivation for expanding further the idea of “Qualitative Multiplicity.”<br

The Mind-Dependence of the Relational Structure of Time (or: What Henri Bergson Would Say to B-theorists) - Deppe, Sonja (Kriterion (Austria), 2016)
Tenseless theorists assert that the relational structure of earlier/later is the essential structure of time. Using B-notions, so they think, we speak about time `as it is' in a metaphysical sense and hence from the outside of our subjective perspective on it. I suggest on the contrary that the relational structure of earlier/later is part of our own intellectual structuring within the access to temporal phenomena. Furthermore it is essentially characterized by the structure of juxtaposition which originates in spatial experience rather than in temporal. In order to show this I consult Henri Bergson's analysis of our temporal experience on the one hand and of our intellectual practice on the other hand. I will conclude that it is not unplausible to take the relational account of time to be more closely connected to the nature of our intellect than to the nature of time itself.<br
Keywords: Philosophy of Time; B-Theorie; Henri Bergson; mind-dependence